3D Printing of Ultrahigh Strength Continuous Carbon Fiber Composites. Issue 2 (6th November 2018) - Parandoush, Pedram; Zhou, Chi; Lin, Dong
Abstract : 3D printing of continuous carbon fiber reinforced thermoplastic (CFRTP) composites is increasingly under development owing to its unparalleled flexibility of manufacturing 3D structures over traditional manufacturing processes. However, key issues, such as weak interlayer bonding, voids between beads and layers, and low volume ratio of carbon fiber, in the mainstream fuse deposition modeling (FDM) and extrusion suppress the applications of these techniques in mission‐critical applications, such as aerospace and defense. This communication reports a novel approach, inspired by laminated object manufacturing (LOM), for 3D printing of continuous CFRTPs using prepreg composite sheets. The prepreg sheets are successively cut based on the sliced CAD geometry, and then bonded layer upon layer using a CO2 laser beam and a consolidation roller system. The void content is low by computed tomography scans and interlaminar bonding strength is as high as conventional autoclave method by lap shear strength tests. The excellent interfacial bonding strength and high volume ratio of continuous carbon fiber contribute to the highest reported tensile strength (668.3 MPa) and flexural strength (591.16 MPa) to date, for all 3D printed CFRTPs. Moreover, the proposed technique also enables controlling the alignment of carbon fiber in printed layers. CFRTPs with unidirectional [0°]s, cross‐ply [0/90°]s, and [0/‐45/0/45°]s fiber reinforcement are produced and evaluated for mechanical properties. The proposed 3D printing method is broadly beneficial for industries requiring high performance and lightweight structural materials with complex geometries. Abstract : A mechanism to 3D print ultrahigh strength carbon fiber reinforced polymer (CFRP) composites capable of achieving aligned continuous carbon fiber reinforcement is presented. The mechanical properties are superior to the existing 3D printed CFRP materials due to an excellent interfacial bonding and minimal void content. During this laser assisted 3D printing technique, temperature at the material interface reaches well above the matrix melting point.